MANAGEMENT DISASTER IN MATERNITY AREAS - Ai Rahmawati; Bhekti Imansari; Devita Madiuw; Ida Nurhidayah; Pipih Napisah; Yanti Hermayanti (Journal of Maternity Care and Reproductive Health, 2019)
Indonesia is one of the countries in the world that is often affected by natural disasters. The disaster has broad-impact such as infrastructure damage, loss of material, and impacts on residents who live in the disaster area including pregnant women, postpartum women, and newborns. The impact that often occurs is stress in pregnant women and postpartum. Also, babies born also may have low birth weight and premature. The purpose of this literature study was to review disaster management in the maternity area in various countries. The electronic database included EBSCO hosts, PubMed and google scholar. Keyword for searching articles was "management disaster", " disaster preparedness " and "maternity area". A total of 859 articles were found and only 15 articles were chosen for analysis. Based on the literature analysis, it was found that there was a need to prepare for a disaster situation, especially women and infants in the maternal period (antepartum, intrapartum, postpartum and neonatal care) in Indonesia. Disaster management divide into three periods, first, before a disaster the government should provide a referral hospital to accommodate maternal patients and teams to deal with maternal problems. When the disaster occurred, identification of disaster victims using the triage OB TRAIN. After a disaster, maternal patients may experience stress and depression. Prenatal depression intervention includes interpersonal therapy, music therapy, and maternal relaxation. Preventing postpartum depression in postpartum mothers is done by breastfeeding their child. There is a need for a design disaster management for maternal patients in Indonesia that consist of three periods: pre-disaster, during disasters, post-disaster.Keywords: Management disaster, disaster preparedness, maternity areas